Hypoglycemic Effect of Andrographis paniculata Extract in Alloxan Induced Albino Wistar Rats: A Systematic Review - Picones, Rinaldi P.; Jr., Romulo R. Macadangdang; Solitario, Jelina Mi-Ann L.; Aguilar, Mary Joy F.; Chang, Mikyla P.; Pangilinan, Nelmina M.; Regulado, Jullie Anne M.; Salazar, Blue Zyrielle S. (Asian Journal of Biological and Life Sciences)
Diabetes or Diabetes Mellitus (DM) is recognized as part of the top leading causes of mortality rates around the globe. The disease is involved with the pancreas which produces insulin. Insulin is crucial in regulating glucose, and as well as fat from the food individuals consume. DM can occur when limited amounts of insulin is produced by the pancreas. It can also occur when insulin is not regulated properly. DM is threat to people of all ages as it can be acquired no matter how old or young a person can be, approximately 90–95 % of people are at risk to have this type of diabetes, due to their imbalanced lifestyle. Therefore, the researchers aim to investigate the effects of Andrographis paniculata; also known as Serpentina, on biochemical parameters of blood sugar level in both alloxan and STZ-induced rats. Experimental and scientific studies conducted on Andrographis paniculata were reviewed from the year 2000 to 2020. A total of ten (10) studies were included in this review, which revealed significant hypoglycemic effects of Serpentina in both alloxan and STZ-induced rabbits and rats. The hypoglycemic activity of Serpentina was due to the active compound (Andrographolide) of the plant and which proved its use in decreasing blood glucose level in all of the reviewed experimental research. Regardless of the presence of known oral hypoglycemic drugs in the market, remedies made from this medicinal herb have been undoubtedly successful to help aid DMII and markedly decreased complications due to lessened side effects.
Keywords: Alloxan-induced; Andrographis paniculata; Blood glucose level; Diabetes Insulin Resistance; Serpentina